2012
DOI: 10.3390/jfb3010061
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse 130 kDa and 260 kDa Recombinant Human Hemoglobin Polymers as Scaffolds for Protein Engineering of Hemoglobin-Based Oxygen Carriers

Abstract: A recombinant 130 kDa dihemoglobin which is made up of a single-chain tetra-α globin and four β globins has been expressed as a soluble protein in E. coli. The sequence of the single chain tetra-α is: αI-Gly-αII-(SerGlyGly)5Ser-αIII-Gly-αIV. This dihemoglobin has been purified and characterized in vitro by size exclusion chromatography, electrospray mass spectroscopy, equilibrium oxygen binding, and analytical ultracentrifugation. The observed values of P50 and nmax for the dihemoglobin are slightly lower than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A second generation product, rHb2.0, has been developed and its efficacy is being evaluated in preclinical trials [12,13]. Furthermore, Marquardt and colleagues prepared di-Hb in which two rHb1.1 units are covalently cross-linked by gene fusion using a peptide linker and they also prepared tetra-Hb that is chemically cross-linked with bismaleimidohexane between a cysteine residue into di-Hb [14]. A pharmacokinetic study in rats demonstrated that the half-life of di-Hb and tetra-Hb are approximately 1.4 and 1.6 times longer than that of rHb1.1 [14,15].…”
Section: Recombinant Hb (Rhb11 Optro®)mentioning
confidence: 99%
“…A second generation product, rHb2.0, has been developed and its efficacy is being evaluated in preclinical trials [12,13]. Furthermore, Marquardt and colleagues prepared di-Hb in which two rHb1.1 units are covalently cross-linked by gene fusion using a peptide linker and they also prepared tetra-Hb that is chemically cross-linked with bismaleimidohexane between a cysteine residue into di-Hb [14]. A pharmacokinetic study in rats demonstrated that the half-life of di-Hb and tetra-Hb are approximately 1.4 and 1.6 times longer than that of rHb1.1 [14,15].…”
Section: Recombinant Hb (Rhb11 Optro®)mentioning
confidence: 99%